A defense of the romantic longing against Hegel’s critique - Moosburger, Laura B. (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
This paper questions Hegel’s critique to the central place that Romantic authors Friedrich Schlegel and Novalis gave to the dimension of affection in their philosophical thinking, as well as to the way they link philosophy and poetry. The summit of this affective and poetical tendency of the Romantics is the so-called Sehnsucht – the infinite longing or aspiration – which Hegel criticizes in a very truculent manner. The interest of this debate is not limited to the studies on the famous controversy Hegel versus Romanticism; in a broader sense, it presents a singular case of a certain dissent on the way how philosophy takes a stand on the matter of affection and poetry. In Hegel’s case, this stand is one that poses a strong hierarchy in which reason and the conceptual activity of thinking are superior to the dimension of feelings, and this hierarchy also unfolds as a superiority of the philosophical over the poetical – while the Romantics endeavoured, precisely, to unravel such hierarchy. This paper defends the importance and deepness of the affective dimension promoted by the Romantics, whilst also attempts to deconstruct some of the main assumptions of Hegel’s critique.